Assessment of the benefits and costs of tourism in Ghandruk, Gandaki, Nepal - Baral, Rekha; Rijal, Deepak Prasad; Saini, Binod Kumar (Haimaprabha, 2023)
Tourism generates both positive and negative impacts to the destinations. Therefore, for maintaining the long term sustainability of tourism industry, tourism impacts should be comprehensively evaluated. However, such assessments are scanty in the Nepalese context. In this study, we assessed the economic, social, and environmental costs and benefits of tourism in Ghandruk, one of the most widely visited iconic tourism destinations both for the domestic and international visitors. Data on various social, economic and environmental benefits/costs were collected via questionnaire survey, group discussion and in person interview and analysed by a Leopold matrix. The results revealed that tourism generates noteworthy economic and social benefits to the destination community, while the negative impacts in all three aspects are minimal. This finding may have broader implications beyond the case study, and suggests that tourism if extended as the primary industry in other similar mountainous villages can play a pivotal role to enhance the socio-economic status of the country.